Análise radiográfica de indivíduos portadores de sobremordida profunda tratados com aparelhos ortopédicos funcionais com equilibrador de Planas (EQUIPLAN) - Bellomo Júnior, Douglas Peres (2005)
Light and intermittent stimulus given by functional orthopedic appliances induce changes on the mandibular dynamics and consequently on its morphology. Discrepancies on the cranium-facial development are predisposing factors. Deep overbite is a malocclusion characterized by an excessive overbite among the anterior teeth. The aim of the present research was to quantify the angular and linear variations of individuals that presented deep overbite and were treated by Planas equilibrator (equiplan). 30 deep bite subjects up to 4 mm were selected in this research whose teleradiographies were taken after and before treatment. This values obtained were analyzed by student t test, ANOVA, Pearson s Correlations Coefficient and Determination Coefficient. All linear measurements increased, lower incisors tip and y growth axis too. No lower and upper incisors intrusion occurs. There were no differences among the cranial basis, the maxilar e mandibular planes, mandibular angle and upper incisors tip. The equiplan was efficient in deep bites treatments, inducing lower molar dento-alveolar growth, not intruding incisors or increasing facial planes divergences.